Economic Impacts of Healthcare in the Rural Health Networks of Florida - Effie Philippakos; Alan W. Hodges; David Mulkey (EDIS)
This is EDIS document FE 339, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2002.